Fires and Fire Safety Measures in Churches of Tobolsk North during the Synodal Period (1722-1917) - O. P. Tsys (Научный диалог)
The results of a study on the extent, causes and measures of combating fires in churches in the north of the Tobolsk diocese in the XVIII - early XX centuries are presented in the article. Sources indicate “large” fires in Berezov and Surgut and few in rural parishes, and, as a rule, they indicate the destruction of church buildings and the futility of public efforts to prevent the fire element. The destruction of churches from fire is presented as a common cause of rebuilding of parish buildings in the 18th century. It is noted that the main cause of the fires was the careless handling of fire by church servants when burning stoves. Fire safety measures are characterized by the adoption of relevant legislative norms and administrative orders, monitoring of building codes and the repair of irregularities made during the construction of churches, and the spread of fire insurance. It is indicated that the state tried to involve not only the police, but also the population in the fight against fires. It is concluded that, despite the efforts made, the fire department in the territory of the region remained at a low level and did not allow to successfully confront the fire element.